Co-created value measuring through the system dynamics and fuzzy logic [Medición del valor co-creado por medio de dinámica de sistemas y lógica difusa] (2014)
The present work proposes a measuring model of the co-created value through the system dynamics and fuzzy logic. In order to identify the variables the co-creation systemic archetype is used and it allows the value elements capture arising from clients' experiences in a case study of a telecommunications company that provides the 4G LTE service. Clients through the bipolar differential methodology make the valuation of value elements using software that allows the register and valuation. Clients express their opinions by the use of linguistic labels defined between two opposite adjectives as a result of a social dialogue. The valuations' results are obtained after the use of the fuzzy inference system, which brings as a result the belonging function of the co-created value variable. The results show that the methodology allows the capture and measure of value elements through illocutionary acts that are proper of the language philosophy.